Evaluation in Peumus boldus trees after 10 years since the harvest: Response in a megadrought scenario - Gangas Fuentealba, Rodrigo; Donoso, Sergio; Espinoza, Claudia; Riquelme, Alejandro; Quintanilla, Miguel; Peña Rojas, Karen (BOSQUE, 2023)
Peumus boldus (boldo) is an important tree in the mediterranean forests of central Chile. Its leaves are valued for their essential oils and alkaloids. Historically, and in various sectors, the harvest of boldo leaves has been superior to natural production. Additionally, the megadrought that has affected these forests since 2010 is see as a threat. Therefore, it is necessary to determine sustainable harvest levels for the management of natural formations with boldo. The objective of the study was to evaluate the recovery of boldos harvested in 2011, in the Metropolitan Region of Chile. The study was carried out in trees with partial harvest, total harvest, and no harvest. Pre-dawn and noon water potential, chlorophyll fluorescence, and growth were evaluated. After 8 years there were still differences between the treatments, where a higher harvest intensity implied a better water condition of the trees. Between 2011 and 2021, partially and fully harvested trees recovered an average of 10.7% and 24.2% of their initial biomass, respectively. The trees without harvest had an average loss of 0.9% compared to the initial biomass recorded in 2011. The reduction of above-ground biomass has been more accelerated since 2019. In the megadrought scenario, it is expected that the growth in boldo will be lower than that reported so far. The climatic conditions in central Chile establish the need to review the harvesting methods and periodicity currently used for boldo.